Scalable Production and Cryostorage of Organoids Using Core–Shell Decoupled Hydrogel Capsules. Issue 12 (22nd November 2017) - Lu, Yen‐Chun; Fu, Dah‐Jiun; An, Duo; Chiu, Alan; Schwartz, Robert; Nikitin, Alexander Yu.; Ma, Minglin
Abstract: Organoids, organ‐mimicking multicellular structures derived from pluripotent stem cells or organ progenitors, have recently emerged as an important system for both studies of stem cell biology and development of potential therapeutics; however, a large‐scale culture of organoids and cryopreservation for whole organoids, a prerequisite for their industrial and clinical applications, has remained a challenge. Current organoid culture systems relying on embedding the stem or progenitor cells in bulk extracellular matrix (ECM) hydrogels (e.g., Matrigel) have limited surface area for mass transfer and are not suitable for large‐scale productions. Here, a capsule‐based, scalable organoid production and cryopreservation platform is demonstrated. The capsules have a core–shell structure where the core consists of Matrigel that supports the growth of organoids, and the alginate shell forms robust spherical capsules, enabling suspension culture in stirred bioreactors. Compared with conventional, bulk ECM hydrogels, the capsules, which can be produced continuously by a two‐fluidic electrostatic cospraying method, provide better mass transfer through both diffusion and convection. The core–shell structure of the capsules also leads to better cell recovery after cryopreservation of organoids probably through prevention of intracellular ice formation. Abstract : A new, capsule‐based platform for scalable production and cryostorage of organoids is reported here. The key to this platform is the core–shell decoupled design of the capsules, which can be continuously produced through two‐fluidic electrospraying. The Matrigel core of the capsules creates a permissive environment for organoid growth while the alginate shell enables the formation of mechanically robust capsules that can be suspended in a stirred bioreactor for biomanufacturing.